Differences Between Sodium Metasilicate and Silicic Acid as Silica Source for Zeolite Y Nano particles Synthesis by Sol- Gel Method - A. Al-Hemiri, Adil; Jawad, Yousif (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Zeolite Y nanoparticles were synthesized by sol - gel method. Dffirent samples using two silica sources were prepared.Sodium metasilicate (Na2SiO3) (48% silica) and silicic acid silica (H2SiO3) (75% silica) were employed as silicasource and aluminum nitrate (Al(NO3)3.9H2O) was the aluminum source with tetrapropylammonium hydroxide(TPAOH) as templating agent.The synihesized-samples were characterized by X-ray diffraction, showed the requirement of diffirent aging time forcomplete crystallization to be achieved. Transmission Electronic Microscope (TEM) images, showed the particles werein the same range of 30 - 75 nm. FT-IR spectroscory, showed the synthesized samples having the zeolite Y crystalproperties. The initial mixing silica to alumina ratio (SiO2/Al2O3) was 10, but, sodium metasilicate sample was of 2.55final ratio, while silicic acid sample have 18.41 and the surface area as tested by BET was of 555.87 m2/g from sodiummetasilicate sample and 276.3 m2/g from silicic acid sample.